Reticulospinal modulation of muscle activation and electromechanical coupling: evidence from the StartReact paradigm - Eilfort, Antonia Maria; Filli, Linard (Frontiers in Human Neuroscience, 2025)
IntroductionMovement initiation relies on descending motor drive conveying motor commands from the brain to spinal motor circuits, leading to the activation of specific muscles to produce the intended movement. While the role of descending motor drive on the onset of muscle activation has been extensively examined, its impact on motor unit recruitment, muscle fiber activation, and the electromechanical delay (EMD) remain poorly understood. This study aimed to elucidate the role of the reticulospinal (RS) system in shaping muscle activation patterns, movement initiation, and the EMD by employing the StartReact paradigm.MethodsThe StartReact paradigm was implemented in 29 healthy participants performing 14 single-joint motor tasks including both upper and lower extremities. Muscle activity was recorded using surface electromyography (EMG), while movement patterns were acquired via motion capture technology. Muscle activation and movement patterns were analyzed in both temporal and amplitude domains to characterize differences between movements cued by either loud (LAS: 120 dB) or moderate acoustic stimuli (MAS: 82 dB). EMD was defined as the time interval between EMG onset and movement initiation.ResultsOur results revealed faster and more pronounced muscle activation and movement performance in response to LAS compared to MAS. Notably, EMD was significantly reduced in LAS trials, suggesting that enhanced RS drive facilitates more rapid electromechanical coupling.DiscussionThese findings suggest that RS drive not only shortens muscular reaction times – characteristic of the StartReact effect - but also modulates muscle activation and movement dynamics in a way that accelerates the transition from muscle activation to movement. The observed reduction in EMD likely reflects changes in motor unit recruitment and muscle fiber activation, highlighting an additional mechanism through which the RS system enables rapid, explosive motor responses. This study provides novel insights into how descending motor drive modulates muscle activation and movement execution, and emphasizes the relevance of the RS system in supporting rapid, high-force movements essential for protective reflexes and athletic performances.